Contribuição do cobogó de terra crua nas condições higrotérmicas dos ambientes internos na edificação - Ferreira, Pablo Raphael de Lacerda (2017)
With the intensification of the urbanization, the crescent demand for materials used in the building of the cities’ edifications passed to be attended by the process of production in wide scale, using a high energy consume. Besides that, the buildings, not always with proper solutions to environmental comfort, began to demand more energy for climatization of interior rooms. In buildings with raw earth, besides de possibility of decrease these environmental impacts, by the process of fabrication of components with low incorporated energy, or by the discard of theirs leavings easily reabsorbed by the nature, may act in favor of a better energetic output during the use of the building. In this context, this research looks for characterize the hollow element made with compressed raw earth stabilized with Portland cement, showing its hygrothermal capacity in to help in the conditioning of the air in internal rooms. The idea is decrease the effects of the dry and hot climate, in which there are a noteworthy daily thermal and hygrothermal amplitude, how happens in the northeast's semiarid of the Brazil. For being a hollow element made with raw earth to be used in buildings facades that may the produced without the use of electric energy, the potential hygrothermal of the material is explored for the air conditioning (relative humidity and temperature) in the interior rooms. The research adopted how strategy the use of the hollow element made in miniature (scale 1:4), to make feasibly the evaluation of the small panels inside of a wind tunnel with hygrothermal controls of relative humidity, varying from 30% to 80%, and temperature, from 20% to 30% in alternated 12 hours cycles. The capacity and speed of absorption and elimination of the air water’s vapor by the material was analyzed. In tests with panels overlapped until 4 layers, with hollow spaces of the elements placed inverted in each layer, doing shunts for the air the cross the panels. Thereat, the research tried to evaluate the efficiency of the system in layers, in the larger interaction between the material and the air, and the consequent potentiality of change the relative humidity and temperature of the air on the opposed side of the panel. With the results was possible to confirm the hygrothermal property of the compressed raw earth stabilized with Portland cement, material of the hollow elements, and to verify that using the panel with three layers, intercalating the empties, there is potential to improve the air quality after crossing the layer system.